Exploring causal correlations between inflammatory cytokines and systemic lupus erythematosus: A Mendelian randomization - Xiang, Mengmeng; Wang, Yilun; Gao, Zhanyan; Wang, Jie; Chen, Qian; Sun, Zhan; Liang, Jun; Xu, Jinhua (Frontiers in Immunology, 2023)
Abstract Objectives: Previous studies have reported that a few inflammatory cytokines have associations with systemic lupus erythematosus (SLE), for example IL-6, IL-17 and macrophage inflammatory protein (MIP). This Mendelian randomization was conducted to further assess the causal correlations between forty-one inflammatory cytokines and SLE. Methods: The two-sample Mendelian randomization utilized genetic variances of SLE from a large publicly available genome-wide association study (GWAS) (7,219 cases and 15,991 controls of European ancestry) and inflammatory cytokines from a GWAS summary containing 8,293 healthy participants. Causalities of exposures and outcomes were explored mainly using inverse-variance weighted method. In addition, multiple sensitivity analyses including MR-Egger, weighted median, simple mode, weighted mode and MR-PRESSO were simultaneously applied to strengthen the final results. Results: The results indicated that cutaneous T cell attracting chemokine (CTACK) and IL-17 may be suggestively associated with the risk of SLE (OR: 1.21, 95%CI: 1.04–1.41, p=0.015; OR: 1.37, 95%CI: 1.03–1.82, p=0.029). In addition, cytokines including beta nerve growth factor (bNGF), basic fibroblast growth factor (FGFbasic), IL-4, IL-6, interferon gamma induced protein 10 (IP10), monokine induced by interferon-gamma (MIG), MIP1b, stromal cell-derived factor-1 alpha (SDF1a), and tumor necrosis factor-alpha (TNFa) are suggestively to be the consequences of SLE disease (Beta: 0.035, p=0.014; Beta: 0.021, p=0.032; Beta: 0.024, p=0.013; Beta: 0.019, p=0.042; Beta: 0.040, p=0.005; Beta: 0.046, p=0.001; Beta: 0.021, p=0.029; Beta: 0.019, p=0.045; Beta: 0.029, p=0.048). Conclusion: This study suggested that CTACK and IL-17 are probably the factors correlated with SLE etiology, while a couple of inflammatory cytokines are more likely to be involved in SLE development downstream.